2010
DOI: 10.1088/0004-637x/711/2/744
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Studies on the Irradiation of Solid Ethane Analog Ices and Implications to Titan's Chemistry

Abstract: Pure ethane ices (C 2 H 6 ) were irradiated at 10, 30, and 50 K under contamination-free, ultrahigh vacuum conditions with energetic electrons generated in the track of galactic cosmic-ray (GCR) particles to simulate the interaction of GCRs with ethane ices in the outer solar system. The chemical processing of the samples was monitored by a Fourier transform infrared spectrometer and a quadrupole mass spectrometer during the irradiation phase and subsequent warm-up phases on line and in situ in order to extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 59 publications
6
37
0
Order By: Relevance
“…Fundamentals corresponding to methane (CH 4 ), acetylene (C 2 H 2 ), ethylene (C 2 H 4 ), the ethyl radical (C 2 H 5 ), 1-butene (C 4 H 8 ), and n-butane (C 4 H 10 ) were assigned in both the ethane (Table 1(a), Figure 1) and D6-ethane ices (Appendix A.1). The detection of 1-butene and n-butane, but not their isomers, is in agreement with previous studies (Jackson et al 1966;Hudson et al 2009;Kim et al 2010) and reaffirms the proposed reaction mechanism of two ethyl radicals forming nbutane followed by dehydrogenation to 1-butene (Section 4). Figure 2 shows that the absorptions in the spectrum from 5000-3350 cm −1 and 2800-500 cm −1 are easily assigned to the reactants and aforementioned products formed within the ethane ice upon irradiation.…”
Section: Infrared Spectroscopysupporting
confidence: 92%
See 3 more Smart Citations
“…Fundamentals corresponding to methane (CH 4 ), acetylene (C 2 H 2 ), ethylene (C 2 H 4 ), the ethyl radical (C 2 H 5 ), 1-butene (C 4 H 8 ), and n-butane (C 4 H 10 ) were assigned in both the ethane (Table 1(a), Figure 1) and D6-ethane ices (Appendix A.1). The detection of 1-butene and n-butane, but not their isomers, is in agreement with previous studies (Jackson et al 1966;Hudson et al 2009;Kim et al 2010) and reaffirms the proposed reaction mechanism of two ethyl radicals forming nbutane followed by dehydrogenation to 1-butene (Section 4). Figure 2 shows that the absorptions in the spectrum from 5000-3350 cm −1 and 2800-500 cm −1 are easily assigned to the reactants and aforementioned products formed within the ethane ice upon irradiation.…”
Section: Infrared Spectroscopysupporting
confidence: 92%
“…The implications of these observations are that ethane bond breaking occurs between carbon-hydrogen bondsbut not carbon-carbon bonds (Section 4). These findings correlate well with results fromprevious studies examining the processing of ethane at astrophysically relevant temperatures; Kim et al (2010) identified the largest molecule formed in the ices as n-butane via recombination of two ethyl radicals using FTIR spectroscopy.…”
Section: Infrared Spectroscopysupporting
confidence: 86%
See 2 more Smart Citations
“…In an analogous reaction sequence, the propanal (C 2 H 5 CHO)-(E)/(Z)-1-propenol [CH 3 CHCH(OH)] tautomer could be synthesized (reactions 8-12). It should be noted that previous experiments demonstrated that the interaction of energetic electrons with ethane led to a carbon-hydrogen bond rupture, but not carbon-carbon bond cleavage (34). Recall that although acetaldehyde and propanal may have some thermal contributions due to their signals, it is important to point out that the enol isomers did not show any increase in intensity during TPD, which reinforces that the enol isomers are formed solely via nonequilibrium pathways during the irradiation phase of the experiment.…”
Section: Resultsmentioning
confidence: 94%